(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the rapidly changing educational landscape, fostering leadership abilities is crucial for the growth and success of students and educators alike. This article explores methods to enhance leadership skills through language education, focusing on the importance of language proficiency in shaping effective leaders. It examines how language learning cultivates critical thinking, communication, and collaboration, which are essential qualities for leadership. By reviewing current research and applying practical approaches, this paper suggests strategies to integrate leadership development into language learning, empowering students to take on leadership roles in their communities and careers